Not (A) Part: Handmade animation, materialism and eco-aesthetic cinema. Issue 1 (1st December 2018) - Smith, Vicky
Not (A) Part is an animated film that draws attention to the decline of flying insects by working with cinematic magnification of the 16mm frame to literal enlargement of their fatalities. Influenced by Stan Brakhage's Mothlight (1963), avant-garde and experimental film theory inform a reading of the formal, poetic and material aspects of the project. Twentieth-century materialist perspectives on the handling of film as reference to labour are brought into contemporary currency to argue that evident methods of physical contact in recent moving image practice establish ecological positions. By emphasizing contact, situated practice, self-inscription and the present tense of making Not (A) Part aligns with eco-aesthetic cinema whilst also allying with broader post-humanist discourse. The article discusses how differing animation methods bring various qualities of movement to small inanimate objects; how a distinct genre of insect animation is established; how, through the interdisciplinary collaborative process, the project, initially rooted in avant-garde film, developed into eco-aesthetic cinema; and finally how the above operations of contact cinema led to new knowledge in the field of film/animation practice.